Dual-tracer constraints on the inverse Gaussian transit time distribution improve the estimation of water mass ages and their temporal trends in the tropical thermocline - H. Guo; W. Koeve; A. Oschlies; A. Oschlies; Y.-C. He; T. P. Kemena; L. Gerke; I. Kriest (Ocean Science)
Quantifying the mean state and temporal change of seawater age is crucial for understanding the role of ocean circulation and its change in the climate system. One commonly used technique to estimate the water age is the inverse Gaussian transit time distribution method (IG-TTD), which applies measurements of transient abiotic tracers like chlorofluorocarbon 12 (CFC-12). Here, we use an Earth system model to evaluate how accurately the IG-TTD method infers the mean state and temporal change of true water age from 1981 to 2015 in the tropical thermocline (on isopycnal layer σ0=25.5 kg m−3). To this end, we compared the mean age of IG-TTD (Γ) derived from simulated CFC-12 with the model “truth”, the simulated ideal age. Results show that Γ underestimates the ideal age of 46.0 years by up to 50 %. We suggest that this discrepancy can be attributed to imperfect assumptions about the shapes of the transit time distribution of water parcels in the tropics and the short atmospheric history of CFC-12. Moreover, when only one transient tracer (CFC-12) is available, temporal trends in Γ might be an unreliable indicator and, due to uncertainties in the mixing ratio, may even be of opposite sign to temporal trends in the ideal age. The disparity between Γ and ideal age temporal trends can be significantly reduced by incorporating an additional abiotic tracer with a different temporal evolution, which we show by constraining Γ with sulfur hexafluoride (SF6) in addition to CFC-12.